(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Insufficient information regarding Alzheimer’s disease (AD) among the healthcare workers can harmfully affect outcomes of the patient. This designate the necessity for constant knowledge supplement on AD among them in order to deliver the best care to AD patients as possible and propose the necessity to evaluate the level of AD understanding among nurses and identify their shortages so as to improve care quality and promote life quality for individuals with AD. Aims of the study: Current study designed to (i) evaluate the knowledge concerning AD among the nurses working in the hospitals of Thi-Qar governorate/Iraq, and (ii) measure the relationship between selected nurses’ demographics and their knowledge on AD. A survey design was applied to assess the nurses’ knowledge regarding AD. (i) Self-designed questionnaire was used to collect Socio-demographic characteristics of the participants which included of 7 items (age, gender, years of experience, educational level, department of work, previous training, and previous caregiving experience). (ii) Alzheimer’s Disease Knowledge Scale (ADKS) were used to assess nurses’ knowledge regarding AD. This study was conducted in four Teaching Hospitals in Thi-Qar governorate /Iraq. A 622 nurses were participated in the study. The results involved answers from 622 nurses. Nurses knowledge was in average (Mean=15.93). Also, there were a statistically significant relationship between certain demographic characteristics (Age, previous training, and previous caregiving experience) and knowledge of the nurses concerning AD. This study exhibited many findings on this important subject, in addition to the demographic characteristics and its relation to nurses’ knowledge.